TRADITIONAL BEVERAGES AS A CULINARY TOURISM ATTRACTION: A STUDY OF TOURIST’S PERCEPTIONS OF LOLOH TERTERAN IN TARO TOURISM VILLAGE, BALI: MINUMAN TRADISIONAL SEBAGAI DAYA TARIK WISATA KULINER: STUDI TENTANG PERSEPSI WISATAWAN TERHADAP LOLOH TERTERAN DI DESA WISATA TARO, BALI - I Gusti Agung Febrianto; Lidjah Magdalena Massenga; Ni Kadek Eni Juniari; I Made Purna Yasa (Journal of Applied Science in Tourism Destination, 2026)
ABSTRACT Purpose : This study aims to examine tourists’ assessments of the quality of Loloh Terteran, a traditional Balinese beverage made from terter leaves (Solanum erianthum), and to identify which product attributes most strongly shape perceived quality in a culinary tourism context. Design/methodology/approach The research employed a descriptive quantitative design. Data were collected through a structured questionnaire distributed to 60 respondents. Consumer assessment was measured using six indicators—price, colour, taste, aroma, perceived benefits, and packaging—rated on a Likert scale. The data were analysed using mean score calculations and interval class interpretation to determine the strength of consumer evaluations. Findings : The overall mean score of 4.24 indicates a very positive evaluation of Loloh Terteran. Colour achieved the highest rating, followed by price, aroma, and taste, all falling within the “strongly agree” category, suggesting that visual appeal, affordability, and sensory attributes constitute the product’s primary strengths. Perceived benefits were rated “agree,” indicating general recognition of functional value. Packaging received a “neutral” rating, highlighting it as the weakest attribute and a potential constraint for market competitiveness. Research limitations/implications : This study is limited by its sample size and focus on a single tourism village. Future research could involve larger samples and comparative studies across destinations. Practically, the findings imply that improving packaging design and informational labeling could enhance product positioning while maintaining traditional authenticity. Keywords: consumer assessmen, traditional beverages, culinary touris, Loloh Terteran, product quality.